1984
DOI: 10.1073/pnas.81.17.5571
|View full text |Cite
|
Sign up to set email alerts
|

Spider venoms inhibit L-glutamate binding to brain synaptic membrane receptors.

Abstract: The venoms from three spider species, Araneus gemma, Neoscona arabesca, and Argiope aurantia, were shown to inhibit the high-affinity, sodium-independent L-glutamate-binding sites in rat brain synaptic membranes. The same three venoms caused concentration-dependent inhibition of the activity of the glutamate-binding glycoprotein purified from rat brain synaptic membranes. The venom milked from the glands of Araneus gemma was the most active inhibitor of L-glutamate binding, causing 60-80% inhibition of both sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The most powerful of them was A. gemma. It was used at a concentration of 0.01 U (amount obtained from a single venom gland), and it caused 60-80% inhibition of 3 H-L-glu binding in GBP or in membranes, and it also was 25 times more powerful than the venom of N. arabesca [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most powerful of them was A. gemma. It was used at a concentration of 0.01 U (amount obtained from a single venom gland), and it caused 60-80% inhibition of 3 H-L-glu binding in GBP or in membranes, and it also was 25 times more powerful than the venom of N. arabesca [38].…”
Section: Discussionmentioning
confidence: 99%
“…Nonspecific binding was determined in the presence of nonlabeled L-glu or GABA (from 10 −4 to 10 −7 M or from 10 −7 to 100 × 10 −4 M, respectively). Specific binding was determined by the subtraction of the averages of nonspecific binding [37,38]. Results were expressed as averages ± SEM of percentages of controls.…”
Section: Binding For L-glu and Gabamentioning
confidence: 99%
“…Although the C1--dependent binding site has been difficult to localize by autoradiography because it is destroyed by freezing (Fagg et al, 1983), it is the most thoroughly studied of ~G l u binding sites. Prior to the description of the specific effect of anions on L-G~u binding , assays were typically done using 50 mM Tris-HC1 buffer (Roberts, 1974;Michaelis et al, 1974;Foster and Roberts, 1978;Baudry and Lynch, 1979a). Thus, much of the earlier work is based on a mixed population of C1-dependent (predominant) and Cl--independent binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications were devoted to a study of the molecular mechanisms of toxins' interaction of with the receptors. A protein named GBP was obtained from synaptic membranes that was able to bind glutamate [67,68]. It was demonstrated that the glutamate binding to this protein was inhibited by the reagents of the FeS groups -NaN 3 , KCN, chelating agents like the o-phenanthroline.…”
Section: Role Of Different Sites Of Toxins' Molecules In Blocking Thementioning
confidence: 99%